Bactericera cockerelli (Sulc), a potential threat to China's potato industry - Oluwashola OLANIYAN (Journal of Integrative Agriculture, 2020)
The potato psyllid Bactericera cockerelli (Hemiptera: Triozidae) has recently emerged as a serious pest of potatoes and other solanaceous crops. It causes direct feeding damage and also vectors Candidatus Liberibacter solanaceaerum (Lso), a pathogen that causes zebra chip disease in potatoes and which potentially costs growers millions of dollars each year. Such producers rely on frequent sprays of pesticides for psyllid control but the results are unsatisfactory and there are negative side effects. The psyllid has spread beyond its native range in southwest US and northern Mexico to Canada, El Salvador, Honduras, Guatemala and Nicaragua via medium to long range dispersal flights perhaps aided by wind currents, and through anthropogenic means. It was accidentally introduced into New Zealand in 2006 and most recently Australia, most likely through the importation of infested plant material. This review summarizes information from studies on the biology, impact and management of B. cockerelli, and highlights the imminent risk of this insect and its associated pathogen invading China, the world's largest producer of fresh potatoes. Development of risk maps leading to increased surveillance, could prevent or delay an incursion and facilitate early detection or eradication should this occur. Long-term management with Lso-tolerant potato cultivars and psyllid control using the parasitic wasp Tamarixia triozae and other natural enemies should be pursued, rather than depending on synthetic pesticides.